Prototipe double acting cylinder transparan sebagai media pembelajaran sistem hidrolik - Tri Pratomo; Rina Dwi Yani; Maryono Effendi; Dovian Iswanda; Alban Naufal; Devi Andriani (Universitas Muhammadiyah Metro, 2021)
Double acting cylinders in its application are widely used in the industry and are often applied in maintenance or repair instruments. The purpose of this research is to design and make a double acting cylinder so that the movement of the hydraulic cylinder its fluid flow can be seen clearly and easily implemented in the movement process, especially in the learning process. The research employs experimental method by directly design a transparent double acting cylinder. This transparent double acting cylinder will later be applied to the hydraulic trainer. The steps taken were determining the transparent material, making material samples for tensile tests, designing and making hydraulic cylinders, conducting hydraulic cylinder tests using Autodesk Inventor 2019. From the test results of hydraulic cylinders made from acrylic using Autodesk Inventor 2019, the minimum pressure that occurs is 1,456 MPa and the maximum pressure that occurs is 6,573 MPa, in operation, the recommended pressure 1,456 to 5,551 MPa, double acting transparent cylinder which has a transparent hydraulic cylinder length of 250 mm, thickness 11.4 mm, hydraulic cylinder inner diameter 32 mm, hydraulic cylinder locking uses 4 bolts with size M8, design pressure 23 kg/cm².Keywords: hydraulic system, double acting cylinder, transparent.